Peripheral brain-derived neurotrophic factor contributes to chronic osteoarthritis joint pain. Issue 1 (January 2020) - Gowler, Peter R.W.; Li, Li; Woodhams, Stephen G.; Bennett, Andrew J.; Suzuki, Rie; Walsh, David A.; Chapman, Victoria
Abstract : Abstract: Brain-derived neurotrophic factor (BDNF) and the high-affinity receptor tropomyosin receptor kinase B (TrkB) have important roles in neuronal survival and in spinal sensitization mechanisms associated with chronic pain. Recent clinical evidence also supports a peripheral role of BDNF in osteoarthritis (OA), with synovial expression of TrkB associated with higher OA pain. The aim of this study was to use clinical samples and animal models to explore the potential contribution of knee joint BDNF/TrkB signalling to chronic OA pain. Brain-derived neurotrophic factor and TrkB mRNA and protein were present in knee synovia from OA patients (16 women, 14 men, median age 67 years [interquartile range: 61-73]). There was a significant positive correlation between mRNA expression of NTRK2 (TrkB) and the proinflammatory chemokine fractalkine in the OA synovia. Using the surgical medial meniscal transection (MNX) model and the chemical monosodium iodoacetate (MIA) model of OA pain in male rats, the effects of peripheral BDNF injection, vs sequestering endogenous BDNF with TrkB-Fc chimera, on established pain behaviour were determined. Intra-articular injection of BDNF augmented established OA pain behaviour in MIA rats, but had no effect in controls. Intra-articular injection of the TrkB-Fc chimera acutely reversed pain behaviour to a similar extent in both models of OA pain (weight-bearing asymmetry MIA: −11 ± 4%, MNX: −12 ± 4%), compared to vehicle treatment. Our data suggesting a contribution of peripheral knee joint BDNF/TrkB signalling in the maintenance of chronic OA joint pain support further investigation of the therapeutic potential of this target. Abstract : Supplemental Digital Content is Available in the Text.Brain-derived neurotrophic factor is expressed in human osteoarthritis synovia. These data provide evidence for its importance as a mediator of osteoarthritis pain.